PENDAMPINGAN SANTRI DALAM MEWUJUDKAN PONDOK PESANTREN BEBAS SCABIES - Narwati, Narwati; Rusmiati, Rusmiati; Thohari, Imam; Suryono, Hadi (Jurnal Pengabdian Masyarakat Sasambo, 2024)
Islamic boarding schools represent a significant site for the educational process of students from diverse backgrounds. The condition of the pesantren does not meet the requisite hygiene standards, posing a significant health risk. Scabies is a dermatological condition that is frequently associated with poor standards of personal hygiene and a lack of access to clean and healthy living conditions. The prevalence of scabies among students at boarding school X is likely to be high, due to a lack of understanding of the importance of personal hygiene and sanitation. The environment exerts a profound influence on public health, particularly in the context of boarding schools. Therefore, it is imperative to consider and enhance the environment. This community service activity aims to provide students with an understanding of how to implement boarding school sanitation through clean and healthy living. Mentoring activities for the students are carried out with lectures related to boarding school sanitation and PHBS, discussions, and demonstrations of antiseptic soap making. The outcomes of the activity are antiseptic soap with coconut and palm oil as ingredients, increased knowledge of personal hygiene among students, PHBS leaflets, and publication in the National Journal.